MEMBANGUN EKOSISTEM PEMBELAJARAN INKLUSIF DAN AKSESIBEL MELALUI PENDEKATAN UNIVERSAL DESIGN FOR LEARNING DI SEKOLAH DASAR - Bunga Syafiq Munira; Jamil Suprihatiningrum; Vivin Ardiyanti; Futry Ayu Lestari; Khristina Antariningsih (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The diversity of student characteristics in elementary schools requires learning approaches that accommodate individual learning needs equitably. Although inclusive education has become a national policy in Indonesia, classroom practices remain largely dominated by standardized instructional approaches, limiting the fulfillment of individual learners' needs. Furthermore, studies examining the implementation of Universal Design for Learning (UDL) in fostering an inclusive and accessible learning ecosystem within Indonesian elementary schools remain limited. This study aimed to analyze the implementation of UDL, identify its supporting factors, and examine the challenges encountered during its implementation. A qualitative approach with an instrumental case study design was employed at SD Tumbuh Yogyakarta. Data were collected through in-depth interviews, classroom observations, and document analysis, and were analyzed using Braun and Clarke's thematic analysis, supported by source and method triangulation. The findings revealed that UDL implementation was realized through six main strategies: flexible co-teaching, differentiated and leveled instruction, theme-based Project-Based Learning, adaptive diagnostic and formative assessment, a rotating supporting educators model, and the provision of accessible infrastructure and learning environments. The novelty of this study lies in conceptualizing UDL as a systemic approach that integrates instructional practices, school culture, stakeholder collaboration, and supportive learning environments. These findings demonstrate that UDL has significant potential to strengthen the quality of inclusive education in Indonesian elementary schools. ABSTRAK Keberagaman karakteristik peserta didik di sekolah dasar menuntut penerapan pembelajaran yang mampu mengakomodasi kebutuhan belajar secara setara. Meskipun pendidikan inklusif telah menjadi kebijakan nasional, implementasi pembelajaran di lapangan masih didominasi pendekatan yang seragam sehingga kebutuhan individual peserta didik belum sepenuhnya terfasilitasi. Selain itu, kajian mengenai implementasi Universal Design for Learning (UDL) dalam membangun ekosistem pembelajaran inklusif dan aksesibel di sekolah dasar Indonesia masih terbatas. Penelitian ini bertujuan menganalisis implementasi UDL, mengidentifikasi faktor pendukung, serta mengkaji tantangan penerapannya. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus instrumental di SD Tumbuh Yogyakarta. Data diperoleh melalui wawancara mendalam, observasi pembelajaran, dan studi dokumentasi, kemudian dianalisis menggunakan analisis tematik Braun dan Clarke yang diperkuat melalui triangulasi sumber dan metode. Hasil penelitian menunjukkan bahwa implementasi UDL diwujudkan melalui enam strategi utama, yaitu co-teaching fleksibel, diferensiasi dan leveling materi, Project-Based Learning berbasis tema, asesmen diagnostik dan formatif adaptif, supporting educators secara rotasi, serta penyediaan infrastruktur dan lingkungan belajar aksesibel. Kebaruan penelitian ini terletak pada penyajian implementasi UDL sebagai pendekatan sistemik yang mengintegrasikan praktik pembelajaran, budaya sekolah, kolaborasi antarpemangku kepentingan, dan dukungan lingkungan belajar. Temuan ini menunjukkan bahwa UDL berpotensi memperkuat kualitas pembelajaran inklusif di sekolah dasar Indonesia.